An Examination of the Biomedical Paradigm: A View of Social Work. Issue 3 (15th April 2016) - Ashcroft, Rachelle; Van Katwyk, Trish
Abstract : The biomedical paradigm provides foundational assumptions that shape the context within which social workers in health care settings practice. By providing social workers with a greater understanding of the history, epistemology, and key assumptions, this article aims to promote critical awareness and critical reflection on how the biomedical paradigm may be influencing health care environments. The analysis of this article raises important questions for social workers within health care environments, questions about how social workers are able to retain their disciplinary identity as agents of change in the pursuit of social justice.